Network theory in finance - Jin, Xiaowei (Nanyang Technological University, 2024)
This research investigates the interconnectedness of the cryptocurrency market, focusing on discerning patterns indicative of potential market crash. Cryptocurrencies often exhibit synchronized price movements, where fluctuations in one asset can trigger corresponding reactions across the market. Through advanced network analysis of historical price data and correlation metrics, this study aims to equip investors valuable insights into the dynamics of the cryptocurrency market, with a focus on identifying interconnectedness patterns that may signal impending market crashes. By establishing a robust framework for recognizing these early warning signs, the study will empower investors with the knowledge necessary to navigate the volatile cryptocurrency landscape effectively, enabling them to make informed decisions and mitigate potential risks.